Kemunculan Aliran-Aliran dalam Agama Menurut Teori Meme Richard Dawkins - Wijarnarko, Andrean Ferry (Jurnal Filsafat Indonesia, 2023)
This research aims to provide an overview of the development of religion in general according to Richard Dawkins' Meme Theory. The problem in this study is the unique phenomenon of the way religion maintains its existence and is accepted by humans along with the times. Meme theory sees the phenomenon of religious development in society beginning with changes in phenomena that appear and then embedded in the human mind. The pattern of change will affect the decisions taken by humans. The pattern of change that occurs in the cultural aspect also occurs in the religious aspect in order to maintain its existence. Allows the emergence of various new sects in the name of a particular religion. This research uses qualitative research methods with a descriptive approach in explaining the emergence of religious schools in self-adjustment with the development of human life in a review of Dawkins meme thinking. The results of research describe Dawkins' reductionist thinking on the development of religion and present Dawkins' thought in viewing the emergence of schools in religion as a result of religious selection and adaptation to problems over time.